2020
DOI: 10.1002/gcc.22882
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and prognostic impact of PAX5 p.P80R in pediatric acute lymphoblastic leukemia patients treated on an AIEOP‐BFM acute lymphoblastic leukemia protocol

Abstract: PAX5 is a member of the paired box (PAX) family of transcription factors involved in B‐cell development. PAX5P80R has recently been described as a distinct genetic B‐cell precursor (BCP) acute lymphoblastic leukemia (ALL) subtype with a favorable prognosis in adults. In contrast, an unfavorable outcome has been observed in children. Our aim was to determine the frequency of PAX5P80R in childhood BCP‐ALL treated according to the Associazione Italiana Ematologia ed Oncologia Pediatrica‐Berlin‐Frankfurt‐Muenster … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
1
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 22 publications
2
13
1
1
Order By: Relevance
“…In order to gain further insight into the potential role of BM stromal cells on the outcome of BCP-ALL, we investigated the prognostic impact of the distribution of such cells in childhood BCP-ALL at different time points after starting therapy, compared to other wellestablished prognostic factors such as MRD [32,[58][59][60][61][62][63][64][65][66][67][68][69] and tumor cytogenetics [70][71][72][73][74]. Interestingly, our results showed that increased percentages of EC within stromal cells found at day +78 of therapy identified a poorer prognosis subgroup of childhood BCP-ALL, independently of the BM MRD status.…”
Section: Discussionmentioning
confidence: 99%
“…In order to gain further insight into the potential role of BM stromal cells on the outcome of BCP-ALL, we investigated the prognostic impact of the distribution of such cells in childhood BCP-ALL at different time points after starting therapy, compared to other wellestablished prognostic factors such as MRD [32,[58][59][60][61][62][63][64][65][66][67][68][69] and tumor cytogenetics [70][71][72][73][74]. Interestingly, our results showed that increased percentages of EC within stromal cells found at day +78 of therapy identified a poorer prognosis subgroup of childhood BCP-ALL, independently of the BM MRD status.…”
Section: Discussionmentioning
confidence: 99%
“…26 Germline mutations are demonstrated as the main drivers of Li-Fraumeni syndrome, which predisposes to a diverse range of inherited rare cancers. 25 Mutations in other genes such as RAS, PAX5, PTEN, EGFR, or MSH6 are involved as predictive markers for poor prognosis in cancers such as pediatric B and T ALL, [27][28][29] AML, 30 gastric adenocarcinoma, 31 glioblastoma, and brain tumors. 32,33 The reported case had relapsed within the first year following the achievement of remission and died after receiving intensive chemotherapy combined with imatinib.…”
Section: Discussionmentioning
confidence: 99%
“…Germline mutations are demonstrated as the main drivers of Li‐Fraumeni syndrome, which predisposes to a diverse range of inherited rare cancers 25 . Mutations in other genes such as RAS , PAX5 , PTEN , EGFR , or MSH6 are involved as predictive markers for poor prognosis in cancers such as pediatric B and T ALL, 27–29 AML, 30 gastric adenocarcinoma, 31 glioblastoma, and brain tumors 32,33 …”
Section: Discussionmentioning
confidence: 99%
“…PAX5 p.P80R confers a poor prognosis in children but is suggested to have a relatively good prognosis in adults. 49,86,87 Taking a broader approach, results from a 250 patient European study advocated 'PAX5-plus' as a new entity, to denote biallelic PAX5 alterations, together with CDKN2A/B deletions and RAS-activating mutations. This group is suggested to have favourable outcomes.…”
Section: Pax5 Alterationsmentioning
confidence: 99%
“…Mutations in PAX5 are often associated with copy number neutral LOH or deletion of the wild‐type allele, and frequently co‐occur with mutations in the RAS or JAK‐STAT pathways as well as FLT3 , BRAF and PIK3CA . PAX5 p.P80R confers a poor prognosis in children but is suggested to have a relatively good prognosis in adults 49,86,87 …”
Section: Lesions Detected Using a Combination Of Molecular Analysesmentioning
confidence: 99%